Os teoremas de Stewart e de Heron e o cálculo da área de um triângulo em função dos lados - Oliveira, Carlos Alberto Maziozeki de (2014)
This dissertation was organized from the observation that mathematical theorems as Stewart’s theorem and Heron’s theorem are rarely used in mathematics classes in middle and high schools. The contributions of these mathematicians in calculating cevians and area of triangles can simplify the solution of many problems. As a starting point, we prepared one extracurricular activity containing four questions centered on Stewart’s theorem and applied the same in three high school classes of CPM-PR. From the analysis of the results of this activity, we defined the literature, the text structure and organization of a collection of applied problems.